Design, Implementation and Evaluation of a Novel Agent-based Control System to Improve Performance of Small and Medium Sized Enterprises: An Industry 4.0 Adoption - Yazdi, Poorya Ghafoorpoor (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Small and Medium-sized Enterprises (SMEs) play a vital role in the world economic structure due to their significant contribution to production, exports and employment. However, there are various financial, marketing and production issues associated with SMEs. This is mainly due to weak traditional manufacturing systems and inflexible control architectures to respond to various market needs. In order to survive, SMEs must be able to overcome the rapid change of the markets and the diverse demands of customers. This involves achieving and maintaining high levels of productivity and the capability to respond rapidly and flexibly in a short lead time. The Industry 4.0 is a current manufacturing trend which improves efficiency, flexibility and agility, and increases the profitability of enterprises by offering different manufacturing paradigms. However, SMEs’ leaders have doubted the benefits of Industry 4.0 for implementation to their manufacturing system. One of the primary design principles of Industry 4.0 is “Decentralized Decisions” which potentially can address the problem of traditional control architecture if implemented. Therefore, this thesis was set out to implement “Decentralized Decisions” to facilitate the Industry 4.0 adoption and improve the efficiency of SMEs. Consequently, a distributed control system was required which was achieved by developing an agent-based control architecture with a Master-Slave mechanism. Lean Six Sigma (LSS) approach was utilized to recognize the limitations, assess, and maximize the system performance after implementing the developed control architecture. It was achieved by measuring the system production time using a time study technique that is used in performance evaluation which is based on Overall Equipment Effectiveness (OEE). A series of solutions were obtained and applied to a system simulation model to assess their influence on maximizing the performance. Since the OEE calculation is based on production time which is proportional to distance between the resources and speed, the corresponding solutions were chosen accordingly. The behavior of the resources in system was different for each solution. Therefore, the solutions were prioritized based on their influence on OEE percentage. The OEE percentage improvements varied from 1% to 15% between the resources. It was observed that considering the highest solution priority for each resource results in maximum system performance. The target system for this research shared the characteristics and features of a SME and the results indicated that implementing the agent-based control architecture along with LSS improved the performance. Implementing both techniques provides a significant step towards successful SME adoption of Industry 4.0 and improves their response to the challenging market. Keywords: Small and Medium Sized Enterprises, Industry 4.0, Agent-based control, Lean Six Sigma, Time Study, Overall Equipment Effectiveness, Simulation Manufacturing Performance measurement

ÖZ: Küçük ve Orta Büyüklükteki İşletmeler (SME'ler) üretim, ihracat ve istihdama önemli katkıları nedeniyle dünya ekonomik yapısında hayati bir rol oynamaktadır. Ancak, SME'lerle ilgili çeşitli finansal, pazarlama ve üretim sorunları bulunmaktadır. Bu, temel olarak zayıf geleneksel üretim sistemlerinden ve çeşitli pazar ihtiyaçlarına cevap vermek için esnek olmayan kontrol mimarilerinden kaynaklanmaktadır. SME’lerin hayatta kalabilmeleri için pazarlardaki hızlı değişimin ve müşterilerin farklı taleplerinin üstesinden gelebilmeleri gerekir. Bu, yüksek verimlilik seviyelerinin elde edilmesini ve sürdürülmesini ve kısa teslim sürelerinde hızlı ve esnek bir şekilde yanıt verebilmeyi içerir. Endüstri 4.0 verimliliği, esnekliği ve çevikliği geliştiren ve farklı üretim paradigmaları sunarak işletmelerin karlılığını artıran mevcut bir üretim trendidir. Bununla birlikte, SME’lerin liderleri, Endüstri 4.0’ın imalat sistemlerine uygulanmasındaki faydalarından şüphe ettiler. Endüstri 4.0'ın ana tasarım ilkelerinden biri, uygulandığında geleneksel kontrol mimarisi sorununu ele alabilecek “Merkezi Olmayan Kararlar” dır. Bu nedenle, bu tez, Endüstri 4.0'ın benimsenmesini kolaylaştırmak ve SME'lerin verimliliğini artırmak için “Merkezi Olmayan Kararlar” uygulamak üzere düzenlenmiştir. Sonuç olarak, Master-Slave mekanizmalı bir ajan bazlı kontrol mimarisi geliştirilerek elde edilen dağıtılmış bir kontrol sistemi gerekli olmuştur. Gelişmiş kontrol mimarisini uyguladıktan sonra sınırlamaları tanımak, değerlendirmek ve sistem performansını en üst düzeye çıkarmak için Lean Six Sigma (LSS) yaklaşımı kullanılmıştır. Genel Ekipman Verimliliği'ne (OEE) dayanan performans değerlendirmesinde kullanılan bir zaman etüdü tekniği kullanılarak sistem üretim zamanı ölçülerek elde edildi. Performansı maksimize etme üzerindeki etkilerini değerlendirmek için bir dizi simülasyon elde edildi ve bir sistem simülasyon modeline uygulandı. OEE hesaplaması, kaynaklar ve hız arasındaki mesafeyle orantılı olan üretim zamanına dayandığından, ilgili çözümler buna göre seçilmiştir. Sistemdeki kaynakların davranışı her çözüm için farklıydı. Bu nedenle, çözümlere OEE yüzdesi üzerindeki etkisine göre öncelik verilmiştir. OEE yüzdesi iyileştirmeleri kaynaklar arasında %1 ile %15 arasında değişmiştir. Her kaynak için en yüksek çözüm önceliğinin göz önüne alınmasının, maksimum sistem performansı ile sonuçlandığı görülmüştür. Bu araştırmanın hedef sistemi, bir KOBİ'nin özelliklerini ve özelliklerini paylaştı ve sonuçlar, LSS ile birlikte ajan bazlı kontrol mimarisinin uygulanmasının performansı iyileştirdiğini belirtti. Her iki tekniğin de uygulanması, Endüstri 4.0'ın SME'lerin başarılı bir şekilde benimsenmesine doğru önemli bir adım atmakta ve zorlu pazara verdikleri tepkiyi geliştirmektedir. Anahtar Kelimeler: Küçük ve Orta Ölçekli İşletmeler, Endüstri 4.0, Agent-based control, Lean Six Sigma, Time Study, Overall Equipment Effectiveness, Simülasyon İmalat Performansı ölçümü
Doctor of Philosophy in Mechanical Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2019. Co-Supervisor: Asst. Prof. Dr. Aydın Azizi and Supervisor: Prof. Dr. Majid Hashemipour
Keywords: Mechanical Engineering; Manufacturing Industry--Small and Medium Sized Enterprises; Computer integrated manufacturing systems; Production engineering; Expert systems (Computer science)--Artificial intelligence; Small and Medium Sized Enterprises; Industry 4.0, Agent-based control; Lean Six Sigma; Time Study; Overall Equipment Effectiveness; Simulation Manufacturing Performance measurement